Is the current UK undergraduate system providing junior doctors knowledge and confidence to manage burns? A questionnaire-based cohort study. Issue 1 (December 2015) - Lemon, Thomas; Stapley, Simon; Idisis, Andrea; Green, Ben
Abstract Background Burns are common in the UK and many of the 30, 000 newly qualified doctors there will be faced with managing them in their first few years of practice. We are concerned that doctors are leaving medical school without adequate teaching on burns and therefore not prepared to manage burns competently. The aim of this study was to assess the graduating doctors self-declared knowledge of basic burns pathology as well as their knowledge and confidence in treating burns. We also wanted to assess whether students felt that their undergraduate course offered burns teaching, either formally or informally. Methods We designed a structured questionnaire with input from two experienced final year medical students, two experienced clinicians and two sociologists. Questions were designed to be open-ended in order to facilitate varied and circumstantiated responses. Final year medical students, due to graduate in June 2014, were invited to take part in a survey with questions on burns management, first aid, pathology, and confidence. These results were then analyzed statistically. Results Of the 300 students invited to join the survey, 244 fully completed the process, representing an 81.3% response rate. Of the respondents over one-third (35%) said they had not received any teaching on burns. And less than half (45%) said they had received formal teaching. Eighty-eight percent of students identified a burn can be caused by a dry heat source; however, 17% of students failed to acknowledge that chemicals are a recognized cause of burns. Only 32% of respondents were confident with management of a burn. Conclusions These results suggest that there is a lack in understanding of burns management, as well as a lack of confidence in treating burns among graduating doctors. There was also a self-identified lack of teaching at an undergraduate level. These concerning results could be improved by the integration of burns into the core medical curriculum.